2004
DOI: 10.1016/j.ejcts.2004.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and prognostic factors in thymic epithelial tumours☆

Abstract: The WHO histologic classification seems to be the most significant prognostic factor reflecting the invasiveness of the thymic tumour. Completeness of resection and Masaoka stage I and II assure a better survival. Unresectable recurrence of thymic tumour predicted a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 24 publications
12
129
3
7
Order By: Relevance
“…41,44 Masaoka stage is a good predictor of aggressive behavior, 10,35,38,44 although recurrences have been documented even with early stage disease. 10,45,46 The proportion of patients with recurrence was higher in stages III and IV compared with patients in stages I and II. 38,45 As most of the recurrent cases in this study were stage I or II at diagnosis, it was not useful in predicting the behavior of these tumors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…41,44 Masaoka stage is a good predictor of aggressive behavior, 10,35,38,44 although recurrences have been documented even with early stage disease. 10,45,46 The proportion of patients with recurrence was higher in stages III and IV compared with patients in stages I and II. 38,45 As most of the recurrent cases in this study were stage I or II at diagnosis, it was not useful in predicting the behavior of these tumors.…”
Section: Discussionmentioning
confidence: 98%
“…10,45,46 The proportion of patients with recurrence was higher in stages III and IV compared with patients in stages I and II. 38,45 As most of the recurrent cases in this study were stage I or II at diagnosis, it was not useful in predicting the behavior of these tumors. In an analysis of 1320 thymic tumors, Kondo and Monden 47 found total resection as the most significant predictive factor.…”
Section: Discussionmentioning
confidence: 98%
“…46,[48][49][50] For instance, studies have shown significantly worse survival of B3 thymoma versus types A through B2 thymoma, 51 types A and AB thymoma, 52 or types A, AB, and B1 thymoma. 53 Recently, a study by Weis et al 54 evaluating 4221 thymomas submitted to the ITMIG retrospective database (including cases between 1983 and 2012) also showed that the WHO classification of thymomas was significantly associated with overall survival in univariate analysis, and although not all thymoma types differed from each other significantly, B3 thymomas had a worse overall survival in R0 resected patients than B1 thymomas. However, after adjusting for age, stage, and resection status, the WHO classification was no longer significant for overall survival.…”
Section: Staging Is Prognostically Superior To Histomorphologic Classmentioning
confidence: 99%
“…14,16,17,[29][30][31][32][33][34][35][36][37][38][39][40] What Levels of 'Best Evidence' Are Currently Available?…”
Section: Resultsmentioning
confidence: 99%